2021
DOI: 10.47162/rjme.62.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Virtual autopsy and confirmation of normal fetal heart anatomy in the first trimester using three-dimensional (3D) reconstruction of histological sections

Abstract: Objective: In this pilot study we tested the feasibility of cardiac structures reconstruction from histologic sections in 12-13 weeks normal fetuses. Conventional autopsy is hampered at this gestational age because of the small size of the heart anatomical structures, while alternative non-invasive methods for pathology examination of the fetus are expensive, rarely available and lack accuracy data regarding the con rmation of rst trimester heart defects.Method: Normal hearts from fetuses aged 12-13 gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Before termination, at 12–13 weeks of gestation, a detailed ultrasound examination was performed by a team of experienced maternal–fetal medicine subspecialists using transabdominal ultrasonography following a previously published protocol 6 using color or high-definition directional power Doppler. 21 A transvaginal approach was used when transabdominal imaging was inadequate. Voluson E10 and E8 systems equipped with RM6C and RIC5-9-D convex transducers were used for the ultrasound examinations.…”
Section: Techniquementioning
confidence: 99%
“…Before termination, at 12–13 weeks of gestation, a detailed ultrasound examination was performed by a team of experienced maternal–fetal medicine subspecialists using transabdominal ultrasonography following a previously published protocol 6 using color or high-definition directional power Doppler. 21 A transvaginal approach was used when transabdominal imaging was inadequate. Voluson E10 and E8 systems equipped with RM6C and RIC5-9-D convex transducers were used for the ultrasound examinations.…”
Section: Techniquementioning
confidence: 99%
“…Congenital malformations affect 8.3% of pregnancies, with the central nervous system, cardiovascular, musculoskeletal, and genitourinary systems being commonly affected (77). A pilot study showed that the fetal heart can be accurately imaged using PM-US, including atria, ventricles, and septum (78). Non-invasive imaging tools can serve as an audit for first-trimester anomalies.…”
Section: Postmortem Ultrasoundmentioning
confidence: 99%